2013
DOI: 10.1017/s0022029913000010
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-type plasminogen activator and plasminogen embedded in casein rule its degradation under physiological situations: manipulation with casein hydrolysate

Abstract: The aims of this study were to test the assumption that tissue-type plasminogen activator (t-PA) and plasminogen (PG) are closely associated with the casein micelle and form a functional complex that rules casein degradation. This assumption was essentially verified for bovine milk under conditions wherein the plasmin system was activated by treatment with casein hydrolysate. It was also shown that urokinase-type PA (u-PA), the second type of plasminogen activator present in milk, was not involved in casein de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Lactose concentration in milk closely reflected both reduction in milk yield and deterioration of milk ability to curdle (Leitner et al, 2011). A recent report on bovine milk provided evidence and suggested that tissue-type PA and PLG are secreted and embedded within the casein micelles and rule its degradation (Silanikove et al, 2013). The unusually high PA:PLG ratio in goat milk can convert rapidly and effectively PLG into PL and explain why it is difficult to record PLG activity in goat milk (Baldi et al, 2002;Leitner et al, 2004b).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lactose concentration in milk closely reflected both reduction in milk yield and deterioration of milk ability to curdle (Leitner et al, 2011). A recent report on bovine milk provided evidence and suggested that tissue-type PA and PLG are secreted and embedded within the casein micelles and rule its degradation (Silanikove et al, 2013). The unusually high PA:PLG ratio in goat milk can convert rapidly and effectively PLG into PL and explain why it is difficult to record PLG activity in goat milk (Baldi et al, 2002;Leitner et al, 2004b).…”
Section: Discussionmentioning
confidence: 96%
“…Collectively, these studies have shown that enzymatic hydrolysis of casein by PL liberates peptides that serve as local regulators of mammary gland functions, which is reflected by simultaneous reduction in milk yield in the infected glands and the inability of the milk of those glands to coagulate (Leitner et al, 2011). Recently, we have shown that tissue type of plasminogen activator Subclinical mastitis in goats is associated with upregulation of nitric oxide-derived oxidative stress that causes reduction of milk antioxidative properties and impairment of its quality Nissim Silanikove ,* 1 Uzi Merin , † Fira Shapiro ,* and Gabriel Leitner ‡ (PA) in cow milk is closely associated with the casein micelles, and that it is responsible for casein hydrolysis (Politis, 1996;Silanikove et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A second category of mechanisms focuses on milk constituents and their by-products as inducers of feedback inhibition of milk secretion. These aged milk mechanisms are supported by evidence of milk constituents that can negatively affect mammary epithelial secretion and survival (52)(53)(54)(55)(56). There appear to be multiple ways in which lactation is regulated locally.…”
Section: Local Feedback Regulation Of Lactationmentioning
confidence: 87%
“…The Silanikove lab (55,56) reported that stress induced an inhibition of milk secretion, which was mediated by production of a proteolytic fragment of b-casein (bCSN1-28). This casein fragment was produced by the action of activated plasmin, and the constituents of this proteolytic pathway (plasminogen activator, plasminogen, plasminogen activator-inhibitor, and plasmin) have been identified in milk.…”
Section: Milk Componentsmentioning
confidence: 99%
“…Leitner et al (2007) argued that the lower concentration of lactose in cows with intramammary infection was also related to the reduction in the secretion of lactose by further conversion of plasminogen to plasmin. This conversion causes the release of β-casein 1-28, which has the ability to block potassium channels, thereby, reducing the release of lactose into the lumen of the mammary alveoli (LEITNER et al, 2004;MOUSSAOUI et al, 2004;SILANIKOVE et al, 2009SILANIKOVE et al, , 2013. Among the possible causes of this influence of mastitis on lactose content could be the utilization of lactose by pathogens, it being an important nutritional substrate (BLUM et al, 2008).…”
Section: Discussionmentioning
confidence: 99%